Antimicrobial Susceptibility Testing in Group B Streptococcus-Positive, Penicillin-Allergic Women. Issue 5 (September 2015) - Wisner, Kirsten
<x xml:space="preserve">Abstract</x> Compliance with some important aspects of the CDC guidelines for prevention of perinatal group B streptococcal disease regarding antimicrobial susceptibility testing in penicillin-allergic women remains unacceptably low. Lack of adherence to some of the details increases risk of harm to newborn babies. Our maternity nursing expert has prepared a brief overview.